Peran Tour Guide, Orientasi Pasar dan Keunggulan Bersaing dalam Mempengaruhi Keputusan Pembelian Wisatawan pada Artshop Dream Ball Silver - Putu Rages Anantha Riyo Prayogi; Putu Ratna Juwita Sari; Komang Sri Widiantari; Ni Putu Nina Eka Lestari (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
The silver handicraft industry in Bali faces increasing competition and market dynamics, particularly in maintaining tourist purchasing interest after the COVID-19 pandemic. Artshops are required to strengthen marketing strategies and competitive positioning to sustain business performance. This study aims to analyze the influence of tour guide roles, market orientation, and competitive advantage on tourists’ purchasing decisions at Dream Ball Silver Artshop, Batubulan Village, Gianyar Regency. A quantitative approach was employed using a survey method involving 170 tourists who had made purchases. Data were collected through structured questionnaires and analyzed using validity and reliability tests, followed by multiple linear regression analysis. The results indicate that the role of tour guides, market orientation, and competitive advantage each have a positive and significant effect on purchasing decisions, both partially and simultaneously. Among the three variables, competitive advantage shows the strongest influence, reflecting the importance of unique design, product quality, and value differentiation in attracting tourist buyers. These findings highlight the strategic role of tour guides as marketing intermediaries, the importance of understanding market needs, and the necessity of strengthening competitive advantages to enhance purchasing decisions and business sustainability in the tourism-based creative industry.